Modeling inhibition effects of Lactobacillus plantarum subsp. plantarum CICC 6257 on growth of Listeria monocytogenes in ground pork stored at CO2-rich atmospheres. (November 2018) - Zhang, Wenmin; Wang, Xiang; Xu, Chaoqun; Chen, Yuanmei; Sun, Wanxia; Liu, Qing; Dong, Qingli
Abstract: This paper aimed to explore and model the combined effects of CO2 atmospheres and Lactobacillus plantarum subsp . plantarum CICC 6257 on growth of Listeria monocytogenes in meat at 25 °C. Before applying the combined treatments, the effects of CO2 and L. plantarum CICC 6257 alone on L . monocytogenes were separately evaluated in broth. It indicated that the maximum population density (Nmax ) of L. monocytogenes could reach 8.52 log CFU/mL within 3 days at 25 °C, even at 100% CO2 concentration; and L. plantarum CICC 6257 alone had no significant (p ≥ 0.05) effect on the lag-phase (λ) of L . monocytogenes . While the combination could, not only prolong the λ, but also reduce the maximum specific growth rate (μmax ) and Nmax of L. monocytogenes in meat. Moreover, the inhibition ability of the combination on L. monocytogenes increased with increasing of CO2 concentrations. The L. plantarum CICC 6257 combined with 60% CO2 was selected as the optimal treatment and the combination had no negative effect on the quality of meat. Finally, the inhibition effects of the combination on L. monocytogenes were well modeled by the modified Logistic model. The study provided a potential approach for bio-protecting meat from L. monocytogenes growth. Highlights: CO2 atmospheres could decrease the umax and increase the λ of L. monocytogenes in broth. L. plantarum CICC 6257 could reduce the umax and Nmax of L. monocytogenes in broth. The combinations could prolong the λ as well as reduce the umax and Nmax of L. monocytogenes in meat. The inhibition ability of the combination to L. monocytogenes increased with increasing of CO2 concentrations. The inhibition effect of L. plantarum CICC 6257 on L. monocytogenes was well modeled.